2015
DOI: 10.3233/jad-150217
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HLA-DR, CD80, and CD86 in Healthy Aging and Alzheimer’s Disease

Abstract: Although monocytes and macrophages could serve as new therapeutic targets for treatment of Alzheimer's disease (AD) and aging of the human innate immune system, its role in the pathogenesis of neurodegenerative disorders such as AD are only poorly understood. We have addressed this here by determining the number of CD14+ monocytes and the frequency of HLA-DR-, CD80-, and CD86-expression in peripheral blood from healthy volunteers aged 20-79 years, and in AD patients at diagnosis and after 12, 30, and 52 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…The HLA class II region is critical in mediating the humoral immune response [11]. Among the genes mentioned above, HLA-DQB1 and HLA-DRB1 are associated with many immunological diseases, such as pemphigus vulgaris [12], narcolepsy [13], Alzheimer’s disease [14], and dermatomyositis [15].…”
Section: Introductionmentioning
confidence: 99%
“…The HLA class II region is critical in mediating the humoral immune response [11]. Among the genes mentioned above, HLA-DQB1 and HLA-DRB1 are associated with many immunological diseases, such as pemphigus vulgaris [12], narcolepsy [13], Alzheimer’s disease [14], and dermatomyositis [15].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have analyzed the expression of these ligands in the elderly. A recent study showed an increase in the basal expression of CD80‐CD86 in immunocompetent individuals aged 70‐79 years compared to those aged 20‐29 years 46 . One proposed explanation for this observation is the chronic inflammation status reported in the elderly (inflamm‐aging), possibly due to dysregulation of the basal state of the transcription factor, NF‐κB 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The DEGs obtained were remarkably enriched in GO terms and pathway under defense response, whole membrane, molecular transducer activity, neutrophil degranulation, ion transport, integral component of plasma membrane, transporter activity and neuronal system. [76], BTK (Bruton tyrosine kinase) [77], C7 [78], PLA2G7 [79], SOCS3 [80], OLR1 [81], LIPA (lipase A, lysosomal acid type) [82], CD86 [83], TLR5 [ [100], AGRN (agrin) [101] and GP6 [102] have been shown as a promising biomarkers in Alzheimer's disease. Field et al [103], Lincoln et al [104], Ziliotto et al [105], El Sharkawi et al [106], Cossins et al [107], Mirowska-Guzel et al [108], Asouri et al [109], Cardamone et al [110], Begovich et al [111], Bennetts et al [112], Iparraguirre et al [113] and Oldoni et al [114] reported that HLA-DPB1, HLA-DQA1, CCL18, CCL20, MMP7, IL1A, IL2RA, CYBB (cytochrome b-245 beta chain), PTPN22, HLA-DMB, ANXA2 and CHIT1expression were associated with progression of multiple sclerosis, but these genes might be liable for advancement of dementia.…”
Section: Discussionmentioning
confidence: 99%